Perencanaan Penyediaan APAR di PT X Berdasarkan Permenakertrans Nomor 4 Tahun 1980 - Indi Febriyanti Vimala; Ratna Ayu Ratriwardhani; Merry Sunaryo; Friska Ayu (Jurnal Media Informatika, 2025)
Fire is an accident that can cause significant losses to humans, assets, and company productivity. PT X, a manufacturing company engaged in the production of metal and plastic, has a high risk of fire due to the use of flammable materials and production activities that generate sparks. This study aims to plan the provision of Fire Extinguishers (APAR) at PT X in accordance with the provisions of Permenakertrans Number 4 of 1980. The use of APAR is crucial for providing initial fire protection as they are easy to operate and can be placed at various strategic points. This study employs a qualitative method with data collection techniques including interviews, observations, measurements, documentation, and literature studies. The study involved three informants. The results show that PT X requires 10 APAR units to ensure optimal protection in production areas including office, workshop, u-bend, plastic, welding, spot welding, metal stamping, warehouse, and assembling. The recommended APAR types are dry powder and carbon dioxide (CO2), effective in extinguishing fires involving solid, liquid, gas, and electrical equipment. The placement of APARs is done considering fire risks and accessibility for quick and safe evacuation. The conclusion of this study is that the implementation of APAR according to the applicable standards is crucial to enhance workplace safety at PT X. Procuring dry powder and CO2 APARs, providing regular training for employees, and conducting routine inspections and maintenance of APARs are essential steps to ensure the company's readiness in facing potential fires. This research is expected to serve as a guideline for PT X in improving workplace safety and minimizing fire risks. Fire is an accident that can cause significant losses to humans, assets, and company productivity. PT X, a manufacturing company engaged in the production of metal and plastic, has a high risk of fire due to the use of flammable materials and production activities that generate sparks. This study aims to plan the provision of Fire Extinguishers (APAR) at PT X in accordance with the provisions of Permenakertrans Number 4 of 1980. The use of APAR is crucial for providing initial fire protection as they are easy to operate and can be placed at various strategic points. This study employs a qualitative method with data collection techniques including interviews, observations, measurements, documentation, and literature studies. The study involved three informants. The results show that PT X requires 10 APAR units to ensure optimal protection in production areas including office, workshop, u-bend, plastic, welding, spot welding, metal stamping, warehouse, and assembling. The recommended APAR types are dry powder and carbon dioxide (CO2), effective in extinguishing fires involving solid, liquid, gas, and electrical equipment. The placement of APARs is done considering fire risks and accessibility for quick and safe evacuation. The conclusion of this study is that the implementation of APAR according to the applicable standards is crucial to enhance workplace safety at PT X. Procuring dry powder and CO2 APARs, providing regular training for employees, and conducting routine inspections and maintenance of APARs are essential steps to ensure the company's readiness in facing potential fires. This research is expected to serve as a guideline for PT X in improving workplace safety and minimizing fire risks.